The Study the Effect of Ultraviolet on the Compression and Hardness Property for Hybrid Material - Abbas, R. A. K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The study was carried out by reinforcing the resin matrix materialwhich was (Epoxy- Ep828) by useing Kevlar fibers and glass fibers type (E-gl ass) both or them in the form of woven roving and poly propylene tlbcrs  in  the form chopped  strand  mats.  wi th (30%)  volume  fraction. Some mechan i cal  properties of the were prepared composite specimens U ltraviolet   radiation  were  stuied   after   being  subjected  to  different weathering conditi ons i ncluded. Compression and hardness testing were carried out using Briel! method so as to compare between composite behavior i n the environments previously mentioned .